Pengaruh Waktu Latihan terhadap Peningkatan Aktivitas Fibrinolisis pada Latihan Aerobik Intensitas Sedang - A. Prastowo, Nawanto (Jurnal Kedokteran YARSI, 2008)
The incremental of tissue-type plasminogen activator (t-PA) level during aerobic exercise is affected by time of the day. Previous studies showed that high intensity of aerobic exercise in the afternoon increased t-PA level higher than exercise in the morning. The purpose of this study was to examine the influence of time of the day on t-PA level during moderate intensity of aerobic exercise. Subjects were 16 sedentary, aged 25-35 years, healthy untrained male, performed two sessions of static ergocycling at 65-70% heart rate maximal (220-age), both in the morning (06.30-08.30) and in the afternoon (15.00-17.00) at least on two days interval. Wilcoxon signed rank test showed t-PA level increased significantly after exercise in the morning (P=0.00) and in the afternoon (P=0.00), but showed no significant difference in the magnitude of t-PA incremental (triangle t-PA) between post-exercise in the morning and in the afternoon (P=0.14). It was concluded that time of the day did not affect the magnitude of the tPA incremental in moderate intensity of aerobic exercise.